Distribution and diet of youngs Albula vulpes (Linnaeus, 1758) (Actinopterygii, Albulidae) in the West margin of the Todos os Santos Bay, Bahia, Brazil - Santos, Edjane Pereira dos; Santos, Alexandre Clistenes de Alcântara (SITIENTIBUS série Ciências Biológicas, 2007)
The bonefish Albula vulpes (Linnaeus, 1758), a resident species of the shallows of bays, estuaries and coastal lagoons was studied during two annual cycles (June 1997 to May 1999), using beach seines, in the West margin of the Todos os Santos Bay aiming at assessing spatial and temporal distribution, and diet of the young of this species. Gut contents were analyzed by Volumetric and Frequency of Occurrence methods combined in Alimentary Importance Index (IAi) in order to verify the importance of each food item. The highest seasonal abundance was recorded in winter related to recruitment in this period of the year, with significant differences being found. The highest spatial abundance was recorded in Bom Jesus, site located in the outer bay. Young of the A. vulpes showed a carnivorous habit, feeding on crustaceans, annelids and organic matter in decreasing order of importance.